Revitalizing Irrigation Systems for Reducing Effects of Climate Change on Irrigated Agriculture in Nepal - Shrestha, Mahesh Man (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Effects of Climate Change (CC) on hydrology and irrigated agriculture in Nepalese irrigation systems will be one of the major constraints in near future in irrigation development. The current status of Nepalese irrigation systems is highlighted briefly with its problems, constraints, challenges and opportunities, and current public policies and regulations in irrigation are summarized briefly with their relevancy and constraints. Reviewing the Agricultural Perspectives Plan (APP) and other policy and strategy frameworks, analyzing its performance and the relevance of its priorities and strategies to the current situation, and based on above facts mitigation and adaptation measures are suggested for short, medium and long-term strategies to revitalize irrigation systems of Nepal for irrigated agriculture enhancement. Suggestions and recommendations to incorporate are made in formulating its principle strategy into a forthcoming Irrigation Policy framework. DOI: http://dx.doi.org/10.3126/hn.v11i1.7225 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.106-111